Improving Students' Self-Confidence and Learning Outcomes in Mathematics Learning Using the Problem Based Learning Model in Class V of SDN 05 Pasaman - Chintia Essa Bella; Hafiz Hidayat; Meria Ultra Gusteti (Journal of Educational Sciences, 2026)
Low student self-confidence and suboptimal learning outcomes are problems in Mathematics learning on data presentation. This study aims to improve student self-confidence and learning outcomes through the application of the Problem Based Learning model. This study is a Classroom Action Research (CAR) conducted in three cycles. Each cycle consists of planning, action implementation, observation, and reflection. The research subjects were 28 fifth-grade students. Data were collected through observation, learning outcome tests, and documentation, then analyzed descriptively quantitatively and qualitatively. The results of the study showed an increase in self-confidence and learning outcomes in each cycle. Students' self-confidence in Cycle I was in the medium to high category, increasing to high in all students (100%) in Cycle II, and in Cycle III as many as 75% were in the very high category and 25% in the high category. The completeness of learning outcomes increased from 39.2% in Cycle I Meeting I to 53.5% in Meeting II, then 64.2% and 78.5% in Cycle II, and reached 89.2% in Cycle III. Based on these results, it can be concluded that using the Problem Based Learning Model can increase students' self-confidence and learning outcomes in Mathematics learning.